Fabrication of chromatographic membrane via surface-grafted membrane for protein separation - Nurul Izwanie, Rasli (2015)
Chromatography process was used extensively for protein separation in biotechnology industry. Chromatography resin bead was normally packed in cylindered column during the operation. However there were limitation on using packed bed chromatography such as high pressure drop, low processing rate and slow binding. Membrane chromatography has ability to overcome the limitation of the conventional packed bed chromatography for protein separation. Membrane chromatography used an adsorptive membrane that carried specific chromatography functionality. In the current study, commercial polyamide (PA) microfiltration membrane was modified with acrylic acid monomer to prepare a membrane chromatography. Two modification methods were compared which are ultra violet (UV) photo grafting and chemical grafting via redox reaction. Modification parameters were studied using One Factor at Time (OFAT) which are initiator concentration (1-50 mM), monomer concentration (0.2-5 M) and grafting time (5-60 minutes). The best grafting technique which gave the highest protein binding capacity was achieved by using UV photo grafting. The highest lysozyme (LZY) binding capacity achieved was 0.175 mg LZY/cm2 membrane for the membrane prepared via UV photo grafting using 10 mM of benzophenone (BP) photo-initiator, 0.1 M of acrylic acid (AA) and 15 minutes of reaction time. The best conditions of UV photo grafting modification obtained from OFAT study were used in Response Surface Methodology (RSM) for optimization of protein binding. Based on the analysis of variance (ANOVA), the quadratic model was chosen with the R squared of the model was 0.9468. The optimum value for each parameter studied in RSM was 20.71 mM of BP, 0.29 M of AA and 18.19 min of grafting time. The optimized membrane chromatography was tested and characterized in term of degree of grafting, contact angle measurement, Scanning Electron Microscope (SEM), Fourier Transform Infra-Red (FTIR), pure water flux and permeability test. The protein binding capacity at optimized condition was 0.180 mg LZY/cm2. This value is less than 4% of the value predicted by the model. This quadratic model can be used successfully to produce the membrane chromatography from PA membrane through UV grafting for LZY binding.